Tsunami Characteristics along The Coast of Biak Island based on the 1996 Biak Tsunami Traces - Yudhicara Yudhicara (Indonesian Journal on Geoscience, 2012)
DOI: 10.17014/ijog.v7i1.135Identification on tsunami traces had been conducted along the coast of Biak Island, Papua, to recognize the character of tsunami potential in this region, referring to the 1996 tsunami event. This study is to observe the influence of tsunami to the environment and tsunami character itself which can be learned from tsunami deposit. According to the 1996 Biak tsunami run up distributions, it can be observed that the maximum tsunami run up was found at the coast which has an undulating to steep morphology rather than other places which has a relatively flat one. The 1996 Biak Tsunami arrival times were approximately between 10 and 15 minutes, such as at the northern and southern coasts of Biak, except for the western one which is about 1 to 5 minutes. This was influenced by the local bathymetry and another possible source triggering tsunami such as a local submarine landslide. The number of tsunami waves were between 2 and 4, and the second one was usually the highest. Based on a sedimentological analysis, the 1996 tsunami deposit is characterized by the dominant coarse sand, while grain size distribution curve shows a character of transportation process similar to an ordinary beach process dominated by saltation current. The foraminifera fossil content tends to indicate that the tsunami deposit was derived from > 200 m seafloor depth (bathyal zone).